The response of natural killer T cells to glycolipid antigens is characterized by surface receptor down-modulation and expansion - Wilson, Michael T. (National Academy of Sciences, 2003)
CD1d-restricted natural killer T (NKT) cells are a subset of regulatory T cells that react with glycolipid antigens. Although preclinical studies have effectively targeted NKT cells for immunotherapy, little is known regarding the early in vivo response of these cells to antigenic stimulation. We have analyzed the early response of NKT cells to glycolipid antigens and bacterial infection by using specific reagents for tracking these cells. Our results demonstrate dramatic in vivo expansion and surface phenotype alterations after NKT cell activation with α-galactosylceramide. In addition, we show significant NK1.1 down-modulation on NKT cells in the setting of oral Salmonella infection. Our results indicate that in vivo activation of NKT cells leads to a dynamic response characterized by surface receptor down-modulation and expansion. These findings alter current understanding of NKT cell biology and should aid in the rational design of NKT cell-based immunotherapies.